Reality is the only genius. The America of Wallace Stevens (Itinera, 2022)
The devastation of truth today at work in the Western world forces those who follow the philosophical and poetic word to rethink the meaning of our stay on Earth and to found a new world in which everyone can live within the space and time opened by the relationship between man and the divine. In this perspective, the poetic work of Wallace Stevens lays the foundations for the birth of that new world America set out to be and which does not have its roots in the illusion of abundance that soon resulted in the most alienating consumerism, but in a reality that preserves in its apparent anonymity the trace of a possible new beginning. «The fundamental difficulty in any art – wrote Stevens – is the problem of the normal». The poet’s task, in fact, is to grasp «the full flower of the actual, not the California fruit of the ideal».